2018
DOI: 10.3390/molecules23102491
|View full text |Cite
|
Sign up to set email alerts
|

Similarity of Data from Bee Bread with the Same Taxa Collected in India and Romania

Abstract: Bee Bread samples from Romania and India were analysed by microscopy and High Performance Liquid Chromatography with Diode Array Detection (HPLC/DAD) and compared with pollen from the correspondent taxa. The quantification of sugars, fructose/glucose ratio, total phenolics and flavonoids was also carried out. From the results was possible to identify Brassica and Eucalyptus samples that present similar HPLC/DAD profiles with the respective ultraviolet (UV) identification of the main compounds as Kaempferol-3-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 50 publications
4
46
2
1
Order By: Relevance
“…10.9 ± 0.9 using a GC-MS analysis, naringenin, kaempferol, apigenin, isorhamnetin, quercetin, and also vitamin E (α tocopherol) in bee bread from Latvia, Russia and Poland. A recent study published by Urcan et al (2018) it was demonstrated that the phenolic profile of BB is identical to the corresponding flora pollen (hand collected) and bee pollen. Despite the biochemical transformation that occurs during the fermentation of the bee bread, the phenolic compounds are unaffected and remain unchanged.…”
Section: Phenolic Compounds Profile Of Bee Breadmentioning
confidence: 91%
“…10.9 ± 0.9 using a GC-MS analysis, naringenin, kaempferol, apigenin, isorhamnetin, quercetin, and also vitamin E (α tocopherol) in bee bread from Latvia, Russia and Poland. A recent study published by Urcan et al (2018) it was demonstrated that the phenolic profile of BB is identical to the corresponding flora pollen (hand collected) and bee pollen. Despite the biochemical transformation that occurs during the fermentation of the bee bread, the phenolic compounds are unaffected and remain unchanged.…”
Section: Phenolic Compounds Profile Of Bee Breadmentioning
confidence: 91%
“…Due to significant differences in terms of the flavonol glycosides content of sea buckthorn berries and leaves, these compounds can be considered as biomarkers for the classification or recognition of sea buckthorn belonging to different species and varieties. It is known that the phenolic composition of plant species depends on its chemotype and on various environmental factors [35].…”
Section: Individual Phenolic and Flavonoid Contentmentioning
confidence: 99%
“…The composition of BB has a major impact when it comes to the flora in the colony's region; it is similar to BP and varies by botanical origin. However, the identification of the main flora can also be analyzed using fingerprints of the phenolic and polyphenolic compounds performed by high performance liquid chromatography with photo-diode array detection (HPLC/DAD) assays [77].…”
Section: Bee Bread (Bb) Composition and Main Bioactivitiesmentioning
confidence: 99%